(untitled) (Communications in Computational Physics, 2008)
Advanced Monte Carlo simulations of magnetisation and susceptibility in 3D XY model are performed at two different coupling constants β =0.55 and β =0.5, completing our previous simulation results with additional data points and extending the range of the external field to twice as small values as previously reported (h ≥ 0.00015625). The simulated maximal lattices sizes are also increased from L=384 to L=512. Our aim is an improved estimation of the exponent ρ, describing the Goldstone mode singularity M(h) = M(+0)+chρ at h → 0, where M is the magnetisation. The data reveal some unexpected small oscillations. It makes the estimation by many-parameter fits of the magnetisation data unstable, and we are looking for an alternative method. Our best estimate ρ = 0.555(17) is extracted from the analysis of effective exponents determined from local fits of the susceptibility data. This method gives stable and consistent results for both values of β, taking into account the leading as well as the subleading correction to scaling. We report also the values of spontaneous magnetisation.